Contribuições da metodologia transdisciplinar para a fundamentação do ensino religioso no contexto da escola laica - Silva, Cícero Lopes da (2013)
This research aims to discuss the relevance of religious education in public schools and secular Brazil. At first develops an analysis of the historical-critical trajectory and evolution of religious education in public schools in the country, highlighting especially the relationship Church and State, National Legislation and lines underlying the pedagogical process. In the second chapter we work with João Décio Passos e Afonso Soares, we suggest three models of Religious Education present in Brazil, the Catechism, the Theological and Religious Studies, which examines the proposal to adopt the model of the Sciences of Religion as the best option to sustain pedagogical and epistemological autonomy of religious education in public schools in the country today. Finally, it is argued the need for a more comprehensive model for the study of religious phenomena through the transdisciplinary approach of Edgar Morin and Basarab Nicolescu, aimed at training the students a perspective of wholeness and citizenship, as expressed in Article 33 of LDB No. 9.394/96, with the new wording of Article 33.